HPLC-DAD-ESI/MS Monitoring of Stilbenes Content in Vranac Red Wines Produced with Traditional and Modern Fermentation Methods - Raicevic, Danijela; Popovic, Tatjana; Ivanova-Petropulos, Violeta; Petreska Stanoeva, Jasmina; Maras, Vesna (Society of Chemists and Technologists of Macedonia, 2020)
Quantification of stilbenes was performed on Vranac wines (vintage 2008 and 2009) produced by traditional and modern fermentation methods, applying different enological additions (enzyme, oak chips and grape tannins). Stilbenes, trans-resveratrol and trans-resveratrol-3-glucoside were determined using the HPLC/DAD/ESI-MS and MS/MS technique. Trans-resveratrol ranged from 0.09 to 3.3 mg/L and the trans-resveratrol-3-glucoside was present in a range of 1.13 to 2.6 mg/L. The influence of vintage, fermentation tanks and enological additions was noticed on the content of stilbenes. Wines from vintage 2008 presented higher amount of stilbenes (on average: 1.89 mg/L) compared to the wines from 2009 (on average: 1.59 mg/L) probably because of the difference in the temperature and humidity in both years. Application of modern fermentation tanks (Sifa and Ganimede) followed by additions of enzyme, oak chips and grape tannins resulted in a higher amount of stilbenes. PCA presented grouping of wines according to the applied fermentation method.